Success and Recurrence Rate after Radial Extracorporeal Shock Wave Therapy for Plantar Fasciopathy: A Retrospective Study. (5th July 2016) - Malliaropoulos, Nikos; Crate, Georgina; Meke, Maria; Korakakis, Vasileios; Nauck, Tanja; Lohrer, Heinz; Padhiar, Nat
Abstract : Background and Aims . The exploration of an individualised protocol of radial extracorporeal shock wave therapy (rESWT) for plantar fasciopathy, assessing success rates and the recurrence rate over a 1-year period after treatment, is not yet identified in literature. Methods and Results . Between 2006 and 2013, 68 patients (78 heels) were assessed for plantar fasciopathy. An individualised rESWT treatment protocol was applied and retrospectively analysed. Heels were analysed for mean number of shock wave impulses, mean pressure, and mean frequency applied. Significant mean pain reductions were assessed through Visual Analogue Scale (VAS) after 1-month, 3-month, and 1-year follow-up. Success rates were estimated as the percentage of patients having more than 60% VAS pain decrease at each follow-up. 1-year recurrence rate was estimated. The mean VAS score before treatment at 6.9 reduced to 3.6, 1 month after the last session, and to 2.2 and 0.9, after 3 months and 1 year, respectively. Success rates were estimated at 19% (1 month), 70% (3 months), and 98% (1 year). The 1-year recurrence rate was 8%. Moderate positive Spearman's rho correlation (r = 0.462, p < 0.001 ) was found between pretreatment pain duration and the total number of rESWT sessions applied. Conclusions . Individualised rESWT protocol constitutes a suitable treatment for patients undergoing rESWT for plantar fasciitis.